Water, Food Security and Agricultural Policy in the Middle East and North Africa Region - Shetty, Shobha (Washington, DC : World Bank, 2022)
The Middle East and North Africa (MNA) region is one of the most water scarce regions in the world, with a regional annual average of 1,200 cubic meters per person (world average is close to 7,000). Water, not land, is now the limiting factor for improving agricultural production in the MNA region. Maximizing water productivity, not yield per unit of land, is, therefore, a better strategy for on-farm water management under such conditions. Raising water productivity requires integrated attention to improving technical, agronomic and management measures. Water User Associations greatly facilitate the implementation of integrated measures. Using satellite remote sensing technologies, planners and policy makers can make more effective decisions to ensure a stable supply of water for food and the environment. All MNA countries with the exception of Morocco are net importers of agricultural products. The greatest benefits for MNA will be generated by comprehensive domestic agricultural reforms, in tandem with higher market access in European and world markets. MNA governments will face issues relating to timing and sequencing of reforms. Given its current resources endowments and growth prospects, it is in the best interest for MNA countries to push towards proceeding with the liberalization of markets in developed countries. At the same time, they could ask for some sort of compensation for higher prices and lost preferences in the form of non-trade distorting financial schemes or even cash grants for those countries facing significant losses as a result. Countries will have to pay a particular attention to the implications of this gradual approach for government revenues, adjustment costs and credibility of reforms.